Front runner - Francis, Felix (G.P. Putnam's Sons, 2015)
"Jefferson Hinkley is back in the newest Dick Francis thriller by the New York Times-bestselling author of Damage. In his role as an undercover investigator for the British Horseracing Authority, Jeff Hinkley is approached by a multi-time champion jockey to discuss the delicate matter of losing races on purpose. Little does he know that the call will set off a lethal chain of events, including the apparent suicide of the jockey and an attempt on Hinkley's own life. Never one to leave suspicious events alone, Hinkley begins investigating the jockey and the races he may have thrown. But there are others out there who intend to prevent his inquiry from probing further. at any cost"--